A new PM2.5-based PM-up method to measure non-mechanical ventilation rate in buildings. (15th July 2022) - Hu, Hao; Huang, Xinjie; Zhao, Yueqi; Qian, Hua; Liu, Cong
Abstract: Air exchange rate (AER) is related with sustainable development of human society. Its convenient measurement in realistic environments remains a challenge due to disturbance for occupants' normal activities. This study developed a new PM-up method to overcome this challenge. This method uses PM2.5 as tracer and determines non-mechanicntal ventilation rate by fitting a model to indoor PM2.5 concentration in an initial bouncing period. Compared to results by mostly used CO2 decay methods, PM-up method has a normalized mean error (NME) of 0.27 and correlation coefficient (r) of 0.69 for AER smaller than 1 h −1 (n = 39). For all the tests (n = 73), NME is 0.35 and r is 0.76. This indicates satisfactory performance of the PM-up method for engineering application. The method's performance seems not impacted by fitting coefficient, AER level, or indoor PM2.5 concentration. We applied the method to continuously measure hourly non-mechanical AER in 6 days, indicating its feasibility in practice. This PM-up method offers new option to measure non-mechanical AER with little disturbance to occupants' normal activities. Highlights: A PM2.5 -based method is developed to measure non-mechanical AER without disturbance. Comparison with CO2 decay method justifies the new method. This method was used to continuously measure hourly natural AER in 6 days in real life. Low CO2 concentration does not guarantee sufficient ventilation.